Knowledge and Adoption of Scientific Livestock Farming Practices among the beneficiaries of Self Help Group Promoting Institutes - Chadda, Akshita; Jadoun, Y.S.; Singh, Jaswinder; Kansal, S.K. (Indian Journal of Dairy Science, 2022)
The current study was conducted in Ludhiana district of Punjab to assess the knowledge and adoption level of scientific livestock farming practices (SLFPs) among the women beneficiaries of Self Help Group Promoting Institutes (SHGPIs) viz., dairy cooperative, government and Non-Government Organization (NGO). Women through livestock based Self-help Groups have involved themselves in different types of income generating activities. Total 120 respondents i.e. 40 from each SHGPI were selected randomly and subjected to structured interview schedule. The findings revealed that majority of beneficiaries of dairy cooperative SHGs had high level of knowledge (45.00%) and adoption (52.50%) about SLFPs followed by medium level among beneficiaries of NGO regarding knowledge (62.50%) and adoption (45.00%).The mean difference in knowledge and adoption between beneficiaries of different SHGPIs was found statistically significant (P<0.01). In case of overall knowledge and adoption about SLFPs, significant difference was observed among the beneficiaries of dairy cooperative, government and NGO based SHGs. Beneficiaries of dairy cooperative SHGs had relatively better knowledge and adoption for scientific livestock farming practices with high mean value as compared to beneficiaries of government and NGO based SHGs. This might be due to more dedication towards services offered by dairy cooperative officials as well as direct contact of beneficiaries of dairy cooperative SHGs with veterinary officers on regular basis as compared to the beneficiaries of government and NGO.